PENGARUH SIKAP KEDISIPLINAN DAN KEJUJURAN PESERTA DIDIK TERHADAP HASIL BELAJAR BIOLOGI - Nurul Fitri; Safei Safei; H. Marjuni (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2016)
This Skripsi study to [regarding/ hit] influence of discipline attitude and sincerity of educative participant to result learn this biologi,Penelitian [is] including quantitative research with Descriptive approach with aim to to know influence of discipline attitude and sincerity of educative participant to result learn Biology class of VIII SMP Country 2 Bajeng West sub-province of Gowa. This Research entangle three variable of yaitudua free variable and one variable tied. the Free variable is discipline attitude and sincerity while variable tied is result learn Biology.Result of discipline attitude analysis obtained average value equal to 85,92 with category of sedang,sikap sincerity obtained average value equal to 75,26 with category is and result of learning Biology obtained average value equal to 80,95 residing in at category very high.Result of statistical analysis [of] inferensial with test of F indicate that value of Fhitung>Ftabel ( 26,09> 3,99), so that Ho refused and [Is] ha accepted meaning discipline attitude and sincerity have an effect on to result learn Biology class of VIII SMP Country 2 Bajeng West Sub-Province of Gowa with contribution equal to 90,5% and the rest 9,5 influenced by other variable which [do] not be packed into this research like enthusiasm learn, motivation learn, style learn and others. To researcher hereinafter, researcher suggest to continue research which similar to seeing other factors which influence result learn and also pay attention the amount of item swampy forest to every used enquette aspect have to flatten. In development of research of researcher shall enhance observation process and interview in course of intake of data and also cooperate with psikolog in development of research.